Implementasi Pendidikan Karakter pada Disabilitas Anak Tunarungu - Juherna, Erna; Purwanti, Endah; Melawati, Melawati; Utami, Yuni Sri (Universitas Hamzanwadi, 2020)
The implementation of character education in children with hearing impairment, especially in the principle of learning children with special needs can be an effective tool in the development of the inculcation of character values. Deaf can be interpreted as a state of hearing loss that results in a person unable to perceive various stimuli, especially through his sense of hearing. In its application, character education is not only oriented towards cognitive aspects, but more oriented to the process of fostering the potential that exists in children, developed through the habituation of good traits in the form of teaching good character values. With the implementation of character education through 3 classical categories to be used as a main reference of them. Among them are the implementation of character education through role models, the implementation of character education through strengthening, and the implementation of character education through habituation.